Study on the digital competencies of prospective pre-school and primary school teachers and the influence of gender and academic performance. - García-Cheikh-Lahlou, Enrique Alastor; Ruiz-Palmero, Julio; Guillén-Gámez, Francisco David (OmniaScience, 2025)
ICT can be a powerful tool for learning, but it is crucial that teachers know how to use it effectively. Digital competence enables teachers to tailor learning to the individual needs of students, making it more engaging and motivating, while creating more meaningful learning experiences. The objectives of this study were: (1) to assess the self-perceived digital competencies of future teachers, considering gender and educational stage, (2) to compare the self-perceived digital competencies of future teachers based on their educational stage and gender, and the interaction between these two factors, and (3) to explore how students’ academic performance influences their digital competencies. This study is a non-experimental, ex post facto analysis with a sample of 897 students from both Infant and Primary School levels. The findings reveal no significant differences in digital competencies between future teachers based on gender, nor in the intersection of gender and educational stage. However, significant differences were found according to educational stage, both in the individual dimensions of the instrument and in overall competence. Primary education students reported higher levels of self-perceived digital competence compared to prospective EFL teachers.
Keywords: Tecnología educativa; Profesores - Formación profesional; Digital competency; Initial training; Educational performance; Educational technology; Gender